CULTURAL LOCALIZATION IN ISLAMIC DA‘WAH: TOWARD A CULTURAL ADAPTATION MECHANISM IN ISLAMIC COMMUNICATION (CAMI) FRAMEWORK - Muhammad Choirin; Ridwan Rustandi; Wahyudin Wahyudin; Hadiyan Hadiyan; Safinah Ismail (J-MD Jurnal Manajemen Dakwah, 2026)
This study aims to examine the global evolution of scholarly discussions on the integration of local culture into Islamic da‘wah and communication practices through a bibliometric and network analysis approach. The research employs a bibliometric study design using 60 Scopus-indexed publications from 2009–2025 as the primary data source. The data were analyzed through co-authorship, co-occurrence, and network visualization techniques to identify thematic trends, collaboration patterns, and conceptual developments in culturally adaptive Islamic communication studies. These patterns reflect a significant increase in publications after 2020, with Indonesia, Malaysia, and the United Kingdom emerging as the leading contributors and international collaboration hubs. The network analysis identifies five major thematic clusters: cultural adaptation in da‘wah, digital Islamic communication, local wisdom and religious identity, transnational Islamic movements, and hybrid cultural expressions. The study further demonstrates a growing transnational convergence of culturally adaptive da‘wah strategies across Southeast Asia, Africa, and the Middle East. In addition, this research introduces the Cultural Adaptation Model of Islamic Communication (CAMI), a conceptual framework explaining how Islamic da‘wah integrates local cultural values and community communication practices while maintaining universal Islamic ethical principles. The study is limited by its reliance on publications indexed exclusively in the Scopus database, which may not fully represent the broader spectrum of global Islamic communication scholarship. Practically, the findings provide a strategic foundation for developing contextual, inclusive, and culturally responsive da‘wah models in multicultural societies. The originality of this study lies in its integration of global bibliometric analysis with the development of the CAMI framework within the field of Islamic communication and da‘wah studies.